A pilot transcriptomic study of a novel multitargeted BRT regimen for anti–MDA5 antibody-positive dermatomyositis: improving survival over conventional therapy - Tokunaga, Moe; Nakai, Yu; Sato, Yoshiharu; Hiratsuka, Mitori; Matsumoto, Yoshinori; Nakatsue, Takeshi; Saeki, Takako; Umayahara, Takatsune; Wada, Jun; Koyama, Yoshinobu (Frontiers in Immunology, 2025)
BackgroundAnti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (MDA5-DM) is associated with severe outcomes, primarily due to rapidly progressive interstitial lung disease (RP-ILD), which is often refractory to standard therapies such as calcineurin inhibitors (e.g., tacrolimus) combined with cyclophosphamide (TC-Tx). This study evaluated the efficacy of a novel multitargeted regimen combining baricitinib, rituximab, and tacrolimus (BRT-Tx) in improving survival outcomes for MDA5-DM patients with poor prognostic factors.MethodsFourteen MDA5-DM patients with multiple adverse prognostic factors were studied. Seven received the BRT-Tx regimen, and the remaining seven, previously treated with TC-Tx, served as historical controls. Twelve-month survival was assessed. Transcriptome analysis was performed for six patients (BRT=3, TC=3), beginning with cluster analysis to evaluate whether changes in peripheral blood gene expression varied according to treatment or prognosis. Gene ontology analysis characterized expression profiles in survivors and distinguished treatment effects. Alterations in the type I, II, and III interferon signatures were also assessed.ResultsIn the TC-Tx group, four of seven patients succumbed to RP-ILD, whereas all seven BRT-Tx patients survived the 12-month observation period. Only one BRT-Tx patient required combined rescue therapies, including plasma exchange, and one case of unexplained limbic encephalitis (LE) occurred. Cytomegalovirus reactivation was observed in both groups (BRT: 5/7; TC: 6/7). Transcriptomic analysis revealed no treatment-specific clustering of differentially expressed genes (DEGs) before and after therapy. However, survivors and nonsurvivors formed distinct clusters, with survivors showing significant posttreatment suppression of B-cell-related gene expression. Moreover, interferon signature scores were significantly lower after treatment in survivors than in nonsurvivors. BRT-Tx effectively suppressed B-cell-mediated immune responses and maintained a low interferon signature, while TC-Tx resulted in nonspecific gene suppression, and in nonsurvivors, an elevated interferon signature was observed.ConclusionBRT-Tx has the potential to improve survival in MDA5-DM patients by effectively targeting hyperactive immune pathways. The combination of rituximab and tacrolimus is expected to disrupt B-cell–T-cell interactions and reduce autoantibody production, whereas baricitinib may suppress both IFN and GM-CSF signaling, regulating excessive autoimmunity mediated by cells such as macrophages. Unlike TC-Tx, BRT-Tx avoids cyclophosphamide-associated risks such as infertility and secondary malignancies. Future randomized controlled trials are warranted to validate its efficacy and safety.